Pengaruh Debit To Equity Ratio (DER) terhadap Return On Asset (ROA) pada PT. Campina Ice Cream Tbk - Ade Ardiansyah; Alwi Alwi; Nurhayati Nurhayati (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study investigates the effect of the Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Campina Ice Cream Tbk for the period 2017–2024 using an associative quantitative approach. Data were obtained from the company’s annual financial statements and analyzed through simple linear regression with SPSS version 25. The results indicate that DER has a significant positive effect on ROA, with a regression coefficient of 0.762. The coefficient of determination (R²) of 0.663 suggests that 66.3% of the variation in ROA can be explained by DER, while the remaining 33.7% is influenced by other factors not examined in this study. Theoretically, these findings reinforce the importance of capital structure in determining corporate profitability. Practically, they imply that PT Campina Ice Cream Tbk must maintain an optimal balance between debt and equity to enhance asset productivity and sustain long-term financial performance.